Underlying the Bias for Human Music Evaluation - Yıldırım, Burak (MEF Üniversitesi, Fen Bilimleri Enstitüsü, 2017)
Predictive analysis is the process of using data analytics to predict the future over historical data. Data analytics is the use of statistical modelling and / or machine learning methods to measure the future. In short, it is one of the data mining techniques for predictive analysis that focuses on creating a predictive model for the future by extracting relationships from the data.
İnsanların müzik değerlendirme basamaklarının ilişkilendirilmesi
Keywords: DEAP; Emotion Analysis; PCA; Over-Sampling; Classification; Duygu Analizi; Sınıflandırma